No Place for Whites? Psychology Students' Reactions to Article on Healing Members of the Stolen Generations in Australia. (December 2013) - Ranzijn, Rob; McConnochie, Keith
<x xml:space="preserve">Abstract</x> This article discusses the emotional reactions of non‐Indigenous psychology undergraduate students to reading a section of an article that was interpreted as suggesting that non‐Indigenous psychologists have no role in Indigenous social emotional well‐being. The students went through an intense process of coming to terms with their reactions through self‐reflection and small group and whole of class discussions, at the end of which they felt reassured that there was a place for non‐Indigenous professionals working with Indigenous clients and communities. The authors suggest that the students were uncomfortable with feeling marginalised and excluded, an unfamiliar feeling for members of the dominant culture. The article discusses strategies that seemed to be successful in managing this discomfort.